Pengakuan Al-Qur’an Dan Hadis Terhadap Hak Asasi Manusia - Fawza Rahmat (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
Human rights are rights inherent in human dignity as human beings created by God Almighty, such as the right to life, the right to achieve a decent life as a human being, the right to freedom and equality. It can be stated more explicitly that among the human rights guaranteed and recognized by the Qur'an and Hadith are personal rights, economic rights, human rights to receive equal treatment before the law and government, political rights, and social and cultural rights. This guarantee and recognition will not change despite various developments and changes in every aspect of life in society.